Self-regulated learning in nursing: A study from a health education course - Keçeci, Ayla (Journal of Human Sciences, 2017)
Background: Self-regulation related to cognition and behaviour is an important factor in learning and academic achievement. Self-regulated learning is defined as the process of learning in which students activate and develop their own cognition, motivation and behaviour through self-regulatory processes. Objectives: The aim of this study was to determine the self-regulation skills of nursing students on a health education course in a state university in Turkey. Methods: The study sample consisted of 110 students who attended the class on the day of the survey and agreed to participate in the study. Data were collected with the Turkish version of the ‘Motivated Strategies for Learning Questionnaire’, which was adapted by Büyüköztürk et al. (2004). Data were analyzed using descriptive statistics such as frequency, percentage and mean, as well as the Mann–Whitney U test, t-test and analysis of variance (ANOVA). Results: The results showed that the participants were motivated by external factors, using the elaboration strategy more frequently than other learning strategies. Second- and third-year students had various motivational levels and preferred different types of learning strategies, and those students who had more positive perceptions of the school, the course and the instructor evinced higher levels of internal responsibility and benefited from learning strategies more frequently. Conclusion: Nursing students were found to be predominantly motivated by extrinsic factors and preferred the elaboration learning strategy.